Changes in crude protein content and amino acids profile in Ginkgo biloba nuts during storage. Issue 1 (1st January 2020) - Zhou, Mengyi; Hua, Tongtong; Ma, Xiaofang; Sun, Haijun
ABSTRACT: Storage is an important issue for ginkgo nuts industry because it is critical to enabling a year-round supply and the next year of cultivation. An investigation into the crude protein content and amino acids profile in ginkgo nuts after different storage times in terms of varieties was carried out in this work. The crude protein content was generally increased during storage while an opposite trend was observed for the concentration of total amino acids. The concentrations of almost all amino acids were more or less decreased except Cys, which was increased 42.13% after 5-month storage, and showed a significant positive correlation with storage time. The effect of storage seemed to be variety-dependent that the variety Tancheng-300 was less prone to fluctuations in amino acids profile amongst the varieties.